Silvicultural systems for broadleaved woodland in Britain - Pryor, S; Savill, P (Oxford Forestry Institute, University of Oxford, 1986)
Conventional clear-felling and replanting is increasingly being recognised as inappropriate for those broadleaved woodlands which have a high value for landscape, amenity and for nature conservation. This prompted an investigation into 'non-plantation', 'uneven-aged' and 'irregular' silvicultural systems, which are, or could be, used in Britain. A new classification of such systems is proposed, with an initial division into coppice and high forest systems. The latter is then subdivided into 'clear-fell', 'shelterwood', and 'selection' systems. 'Group' and 'strip' variants of each of these three can then be identified. All systems can use planting, natural regeneration or a combination. For each system the following is presented: i) a description based on European use, ii) an account of British examples, iii) discussion of techniques, iv) analysis of profitability, v) evaluation of benefits for landscape, amenity and conservation. No really convincing examples of selection and shelterwood systems could be found in Britain, but some efficient group shelterwood and group selection systems exist. The failure of natural regeneration should be tackled by concentrating on prolific-seeding species such as ash and sycamore rather than oak and beech, and by more thorough preparation for good seed years especially by cultivation and careful management of overstorey density. Although establishment costs for shelterwood systems were lower than for clear-fell, the overall profitability for oak was similar. The Net Present Values of some 'low-input' options, such as simple coppice, were surprisingly high. Most profitable of all was an ash/sycamore shelterwood system. For landscape and conservation, coppice, or group systems using natural regeneration, are probably the most beneficial. A uniform shelterwood system can be as undesirable as a clear-fell and replant operation if very intensively managed. The establishment of long-term trials of the various systems is recommended, and more information is needed on the effect of degrees of canopy shading on weed and seedling growth.